DIVERSIFIKASI PRODUK OLAHAN UDANG REBON PADA KELOMPOK WANITA NELAYAN - Sri Mardiyati; Amruddin Amruddin (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2016)
Target outcomes of the activities ofdevotion to community especially for women fishers groups among others: (1) Increasing knowledge of women fishers on insight entrepreneurship and diversification of processed food products; (2) Increasing the skills of women fishers in processing a variety of processed foods based Acetes; (3) The creation of refined products such as shrimp paste Acetes more hygienic and healthy and have attractive packaging and branding; (4) The creation of Acetes processed product diversification, which can follow the changing tastes of consumers, such as crackers, nuggets, and grilled fish cake. To achieve the target outcomes are expected, then the method of execution used in this devotion activity is a method of counseling and training, dedicated primarily to the women fishers group. Results of this devotion to community program, among others: (1) Implementation of the devotion program is generally run well (both partners very positive response); (2) This devotion program has considerable benefits, especially for coastal communities are still low income, so they can increase their income; (3) The devotion program  have generally been able to increase the knowledge and skills of the women fishers about the science of entrepreneurship, diversification of processed food based Acetes (nugget, grilled fish cake, crackers, shrimp paste), and techniques prosessing, packaging, labeling and branding the good one; (4)The women fishers are mostly interested and keen to develop business-based processed food diversification Acetes, either independently or in groups, because of the availability of local raw materials are quite abundant.Keywords:  Acetes, women fishers, product diversification